Critical Evaluation of the Ultrsdonographic Biophysical Profile Score, Their Interpretation and Value. Hospital Guillermo Almenara, Lima-Perú - Alegría Guerrero, Raúl (1999)
OBJECTIVES: To make a critical evaluation of the performance of Ultrasonographic Biophysical Profile (UBP) as a method for antepartum fetal evaluation; to define their main outcome measures as well as their interpretation, and propose a fetal well-being assessment algorithm which considers the score obtained. MATERIAL AND METHODS: Observational, prospective blind study. Since october, 1997 to september, 1998, 120 women with a gestational age ³28 weeks who required fetal well-being assessment to decide pregnancy interruption, at the High-Risk-Obstetrics Department, Hospital Guillermo Almenara, Lima. We evaluate the difficulties and benefits obtained with the ultrasonographic assessment of baseline fetal heart rate and heart reactivity; and the value of ultrasonographic qualitative assessment of amniotic fluid volume, placentary senescence and early placentary aging; and the value of establishing a cutpoint to define high risk pregnancies. RESULTS: Using this way, UBP showed an high sensitivity (87,5%), a good predictive value (63,6%) and an important decrease of false positive and false negative results (36,3% and 2,0%, respectively). CONCLUSIONS: Used in conjunction with a fetal well-being assessment algorithm and with an individualized approach to each woman, UBP was efficient and effective.